2021
DOI: 10.2147/opto.s328787
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Cationic Emulsion to Control the Tear Film Evaporation Rate

Abstract: Purpose To investigate the effect of a single application of cationic emulsion in controlling tear film evaporation and improving tear quality and quantity. Materials a Methods Twenty male subjects diagnosed with DE were enrolled in the study with an average age of 45.8 ± 6.37 years. The tear film parameters were observed at several time points post-instillation of the cationic emulsion (10, 20, 30, and 60 min). The tear evaporation rate (TER) was measured with a VapoMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This can be particularly useful for patients with DED affecting the TFLL such as MGD. Two recent studies confirmed that a single drop of CE‐based AT resulted in an increase in the tear film volume in healthy individuals and in males subjects with DED (Abusharha, 2021; Makri et al., 2021). The outcomes also revealed that tear film stability is enhanced after a single instillation of CE‐based AT, which can effectively control the evaporation rate (Abusharha, 2021).…”
Section: Clinical Studies Assessing the Different Modes Of Actionmentioning
confidence: 82%
“…This can be particularly useful for patients with DED affecting the TFLL such as MGD. Two recent studies confirmed that a single drop of CE‐based AT resulted in an increase in the tear film volume in healthy individuals and in males subjects with DED (Abusharha, 2021; Makri et al., 2021). The outcomes also revealed that tear film stability is enhanced after a single instillation of CE‐based AT, which can effectively control the evaporation rate (Abusharha, 2021).…”
Section: Clinical Studies Assessing the Different Modes Of Actionmentioning
confidence: 82%